Probiotic and prebiotic mechanisms in IBD-associated colorectal carcinogenesis: recent advances - Fan, Xueru; Wang, Xiaoge; Chao, Yang; Xu, Erping (Frontiers in Nutrition, 2026)
Inflammatory bowel disease (IBD), a chronic relapsing inflammatory disorder of the gastrointestinal tract, significantly increases the risk of progression to colorectal cancer (CRC). Emerging studies highlight the critical roles of gut microbial dysbiosis and sustained intestinal inflammation in driving this pathological transformation. Probiotics and prebiotics, as modulators of gut microbial ecology, have attracted considerable attention as potential interventions to restore microbial balance, regulate immune responses, and mitigate carcinogenic processes. In this review, we integrate the interplay mechanisms among inflammation, microbiota, and immunity in IBD-associated colorectal carcinogenesis (IBD-CRC), with a focus on the roles of probiotics and prebiotics in microbial remodeling, enhancement of epithelial barrier integrity, inhibition of inflammatory signaling, and activation of antitumor immunity. Furthermore, we discuss preclinical and clinical evidence supporting their efficacy in delaying or preventing IBD-CRC. The review also provides perspectives on future customized synbiotic strategies in microbiota-targeted therapy and cancer prevention.